2013
DOI: 10.21307/eb-2013-005
|View full text |Cite
|
Sign up to set email alerts
|

Managing Madness: Mental Health and Complexity in Public Policy

Abstract: This paper explores the concept of collaborative care, particularly in relation to a range of new models of organisation and service that are emerging in response to one of the most problematic areas of public policy -mental health. These emerging models of coordinated mental health care are testing the limits of the evidence supporting coordinated care, and require critical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…With rates of mental disorders rising among young people, primary mental health services have been required to support those with more complex presentations without the backup of more specialist systems of care (Rosenberg and Hickie, 2013). Furthermore, although clinical complexity has long been a critical consideration in care planning and delivery, there has been no consensus, consistent definition, or established operational model of what complexity entails.…”
Section: Discussionmentioning
confidence: 99%
“…With rates of mental disorders rising among young people, primary mental health services have been required to support those with more complex presentations without the backup of more specialist systems of care (Rosenberg and Hickie, 2013). Furthermore, although clinical complexity has long been a critical consideration in care planning and delivery, there has been no consensus, consistent definition, or established operational model of what complexity entails.…”
Section: Discussionmentioning
confidence: 99%
“…This care was mostly provided by different health care providers from different organizations. In this context of increasingly specialized and cut up care, integrated care does not sufficiently develop (Rosenberg & Hickie, 2013). Flexible interactions between stakeholders is needed (Ellis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such programs have yet to materialize at scale ( Johansen and Thylstrup, 2019 ). While there are presumably also several causes for this lack of holistically oriented services it has been suggested that progress has been hampered by lack of engaging with the breadth of processes involved in a decentered treatment system ( Rosenberg and Hickie, 2013 ; Priebe, 2016 ). Figure 1 places the important developments in relation to each other.…”
Section: Dual Diagnosis: Emergence Of a Fieldmentioning
confidence: 99%